Comparative assessment of complex stabilities of radiocopper chelating agents by a combination of complex challenge and in vivo experiments - Litau, Shanna; Seibold, Uwe; Vall-Sagarra, Alicia; Fricker, Gert; Wängler, Björn; Wängler, Carmen (ChemMedChem, 2015)
For 64Cu radiolabeling of biomolecules to be used as in vivo positron emission tomography (PET) imaging agents, various chelators are commonly applied. It has not yet been determined which of the most potent chelators-NODA-GA ((1,4,7-triazacyclononane-4,7-diyl)diacetic acid-1-glutaric acid), CB-TE2A (2,2′-(1,4,8,11-tetraazabicyclo[6.6.2]hexadecane-4,11-diyl)diacetic acid), or CB-TE1A-GA (1,4,8,11-tetraazabicyclo[6.6.2]hexadecane-4,11-diyl-8-acetic acid-1-glutaric acid)-forms the most stable complexes resulting in PET images of highest quality. We determined the 64Cu complex stabilities for these three chelators by a combination of complex challenge and an in vivo approach. For this purpose, bioconjugates of the chelating agents with the gastrin-releasing peptide receptor (GRPR)-affine peptide PESIN and an integrin αvβ3-affine c(RGDfC) tetramer were synthesized and radiolabeled with 64Cu in excellent yields and specific activities. The 64Cu-labeled biomolecules were evaluated for their complex stabilities in vitro by conducting a challenge experiment with the respective other chelators as challengers. The in vivo stabilities of the complexes were also determined, showing the highest stability for the 64Cu-CB-TE1A-GA complex in both experimental setups. Therefore, CB-TE1A-GA is the most appropriate chelating agent for *Cu-labeled radiotracers and in vivo imaging applications.